AN OVERVIEW OF OUTPATIENT SERVICE QUALITY AT RSIA AISYIYAH SAMARINDA IN 2025 - Mudassir Yunus; Nur Rohmah; Rahmat Bahtiar; Ratno Adrianto (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background: Service quality is a crucial factor for patient satisfaction and loyalty in healthcarefacilities. The Government of Indonesia, through the Minister of Health Decree (Kemenkes) RI Number 129/Menkes/SK/II/2008, has set Minimum Service Standards (SPM) for outpatientsatisfaction at ≥90%. A study in 2024 showed a relationship between service quality and patientsatisfaction at RSIA Aisyiyah Samarinda, and an internal survey report for the January-June 2024 periodindicated that outpatient patient satisfaction was still below the 90% threshold. Objective: This study aims to provide an overview of outpatient service quality at RSIA AisyiyahSamarinda in 2025. Methods: This was a descriptive quantitative study usingaccidental sampling technique, with data collected from 110 respondents (n=110). The service qualityvariable was measured using five dimensions (Tangibles, Reliability, Responsiveness, Assurance,Empathy). Results: The results showed that the overall average service quality at RSIA Aisyiyah Samarindareached 90.6%, which falls into the “Very Good” category and meets the minimum standards set bythe Ministry of Health (Kemenkes). The dimensions that exceeded the standard were Assurance (92.5%), Empathy (92.1%), and Reliability (91.0%). However, two dimensions remained below the90% threshold, namely Responsiveness (89.3%) and Tangibles (88.0%). Conclusion: The overview of outpatient service quality at RSIA Aisyiyah Samarindain 2025 was categorized as very good